Political participation of ethnic minority groups in Malaysia - Fang, Yi Xue (2016)
The marginalization of ethnic minorities in socio-economic and political developmentshas raised concerned in Malaysia. The current government mobilizes attention to them especially during the election period due to their significant contribution in securing a number of parliamentary seats. Nevertheless, the participation of the Orang Asli group in the street demonstration recently for example, had sent a message of discontentment on the policies implemented. The questions raised were to what extent of the political participation of the minorities in order for them to sustain their needs. Hence, this study aims to (1) determine the level of political participation of the ethnic minorities (2) anticipate support of the minorities in the GE-14 and (3) determine the relationship between respondents’ backgrounds (income and education) and the level of political participation. The level of political participation was measured using voting status in GE-13, involvement in political party and political activities while their support was evaluated from their voting intention in GE-14. A quantitative approach was employed using survey. There was 610 respondents involved from six ethnic minority groups namely Baba Nyonya, Portuguese, Chitty, Siamese, Sikh and Orang Asli in Peninsular Malaysia. The survey data was analyzed using descriptive analysis and Pearson correlation. The level of political participation was determined by measuring total score of participation in political activities. The support of the ethnic minority groups was cross-tabulated using descriptive analysis. Furthermore, the relationship between the level of political participation and the income and education background were examined using the Pearson correlation test. The results showed that all ethnic minority groups participated moderately in politics. The Orang Asli, Siamese and Chitty intend to support the BN government in the next GE-14 while the Baba Nyonya, Portuguese and Sikh community were less supportive. Therefore, the support of the ethnic minority groups towards the current ruling government is not convincing despite of the government claimed of giving supports to them. The result showed that there is no significant relationship between both variables of income and education with the level of political participation. The moderate participation of these ethnic minority groups in politics could possibly answer the problems of them being disadvantaged in many areas.